2019
DOI: 10.2174/1389203720666190104123210
|View full text |Cite
|
Sign up to set email alerts
|

ConBr, the Lectin from Canavalia brasiliensis Mart. Seeds: Forty Years of Research

Abstract: Lectins are defined as proteins or glycoproteins capable of specific and reversible binding to carbohydrates. Inside this group of proteins, the most well-studied lectins belong to the Leguminosae family, and inside this family, the Diocleinae subtribe includes the most characterized lectin Concanavalin A (ConA), as well as ConBr, the lectin from Canavalia brasiliensis, the subject of this review. Since 1979, several studies have been published in the literature regarding this lectin, from its isolation and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…After addition of Ca 2+ or Mn 2+ ions, a partial restoration of the activity was observed, while full activity was recovered only after the addition of both divalent cations. These results show that CsL, similar to most Diocleinae lectins, is dependent on metal ions, such as Ca 2+ and Mn 2+ (Figure 3CD and Table 3) [7,51]. Judging from the absence of PAS staining CsL, does not have any covalently attached glycan in its structure in contrast to the positive control lectin (VML) (Figure 4) [52,53].…”
Section: Lectin Characterization 13mentioning
confidence: 81%
“…After addition of Ca 2+ or Mn 2+ ions, a partial restoration of the activity was observed, while full activity was recovered only after the addition of both divalent cations. These results show that CsL, similar to most Diocleinae lectins, is dependent on metal ions, such as Ca 2+ and Mn 2+ (Figure 3CD and Table 3) [7,51]. Judging from the absence of PAS staining CsL, does not have any covalently attached glycan in its structure in contrast to the positive control lectin (VML) (Figure 4) [52,53].…”
Section: Lectin Characterization 13mentioning
confidence: 81%
“…ConBr and ConA display high similarity of amino acid sequence and crystal structure. However, differences of biological activities have been well documented for these lectins [33,34]. Moreover, other lectins of the genre Canavalia, such as CaBo and ConV, showed similar effect only after 24 h treatment and at higher concentration (50-100 μg/mL) [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…It is a glucose/mannose-specific lectin largely homologous to ConA, differing by only three residues [31,32]. Numerous studies have shown various biological actions of ConBr on different targets, including immune and nervous system cells [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…They may form ion channels in the microbial membrane or inhibit adhesion of microbial proteins to host polysaccharide receptors. Hence, they are capable of precipitating polysaccharides and glycoproteins or agglutinating cells [82][83][84][85]. Overall, these changes are mostly induced by hydrophobic effects, covalent binding and hydrogen binding of their phenolic compounds [69].…”
Section: Plant-derived Biomoleculesmentioning
confidence: 99%
“…Regardless, these proteins or glycoproteins are often positively charged, with disulphide bonds. Concanavalin A and galectin-1 are well-known examples, having as ligands Manα1-OCH 3 and Gal(β1→4)Glc, respectively [82][83][84][85]90].…”
Section: Plant-derived Biomoleculesmentioning
confidence: 99%